1998
DOI: 10.1007/s004670050488
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-12 and interferon-γ production in childhood idiopathic nephrotic syndrome

Abstract: Cellular immune disturbances, and T lymphocyte function in particular, have been previously implicated in idiopathic nephrotic syndrome (INS) of childhood. There are different patterns of cytokine expression in various forms of glomerulonephritis, which suggests that local production of these peptides plays an important role in the pathogenesis and progression of glomerulonephritis. To investigate T-cell and monocyte/macrophage cytokine production in INS, interleukin-12 (IL-12) and interferon-gamma (IFN-gamma)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 12 publications
5
16
1
2
Order By: Relevance
“…On the other hand, the IL-12R 1 chain was normally expressed. The downregulation of the IL-12R 2 is compatible with the low IL-12 cytokine level, as previously reported by Stefanovic et al [38] and the lack of induction of the Th1 transcription factor T bet that we observed during relapse (unpublished data). These observations, as well as several published reports, support the hypothesis of Th2 polarization during MCNS.…”
Section: T Cell Signal Transduction In Mcnssupporting
confidence: 92%
“…On the other hand, the IL-12R 1 chain was normally expressed. The downregulation of the IL-12R 2 is compatible with the low IL-12 cytokine level, as previously reported by Stefanovic et al [38] and the lack of induction of the Th1 transcription factor T bet that we observed during relapse (unpublished data). These observations, as well as several published reports, support the hypothesis of Th2 polarization during MCNS.…”
Section: T Cell Signal Transduction In Mcnssupporting
confidence: 92%
“…Hence reported data may not represent the true level of cytokines. However, several reports have demonstrated elevated or reduced levels of IL-2, IFN-g, IL-4, and IL-10 in the supernatant of in vitro mitogen-stimulated peripheral blood mononuclear cells (PBMC) derived from children in the acute phase of MCNS, suggesting that the pathogenesis of MCNS might be associated with activation of both Th1 and Th2 cells [2,5,6,10,11,14]. However, these in vitro studies may not accurately represent the true in vivo production of cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies focusing on Th1 or Th2 cytokine profiles in INS have measured serum or urine level of cytokines such as interleukin (IL)-1, IL-2, IL-4, IL-8, IL-10, IL-18, tumor necrosis factor (TNF)-a, and interferon (IFN)-g [1,4,6,9,10,11,12,13,14,15]. The potential involvement of IL-2 has been investigated most frequently in the pathogenesis of INS.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the mechanisms of action of immunoglobulin are blockade of Fc receptors on monocytes/ macrophages and neutrophils [15], suppression of cytokine production and neutralization of cytokines [16,17], inhibition of complement activation [18], anti-idiotypic suppression [19], downregulation of B-and T-cell functions [20], and neutralization of superantigens [21]. It has also been suggested in many reports that T-cells, cytokines and transcription factors may be important in the pathogenesis of idiopathic NS [22][23][24][25][26]. Our previous study revealed that, although high-dose immunoglobulin had no effect on biochemical characteristics of NS in rats, the glomerular sclerosis index was significantly lower in the group treated with immunoglobulin than in the control group [27].…”
Section: Introductionmentioning
confidence: 98%